JUDGES TYPES OF JUDGES' QUESTIONS IN EVIDENTIARY HEARINGS AT THE DISTRICT COURT: TIPE PERTANYAAN HAKIM DALAM SIDANG AGENDA PEMBUKTIAN PERKARA DI PENGADILAN NEGERI - Asri Wahyuni Sari; Ria Satini; Rina Sartika (LLDIKTI Wilayah X, 2024)
This article examines the types of questions used by judges in the legal process at the District Court, especially in criminal case involving five police officers in Indonesia of murder case. The trial took five months, from September 2022 to March 2023. one of the reasons for the length of the trial process was because the defendant did not honestly provided information and statements. The judge as the interrogator must have interrogation skills so that the evidence and statements from witnesses can prove that the defendant committed the crime. This research is qualitative research with a case study method. The criminal case for the murder of Joshua Hutabarat was used as a data source and the judge's speech with the defendant during the trial was used as data. There were three trial videos analyzed, namely the judge's speech with the defendant Ferdi Sambo, the judge with Richard Eliezer and the judge with Putri Candrawinata. Data collection uses recording and recording techniques as well as documentation. The results of the research explain that the tendency of the question patterns given by judges is 385 open questions and 260 closed questions. Based on these findings, it was concluded that the judge asked questions using an open, productive pattern of questions to seek evidence/information regarding the truth of the perpetrator's involvement. However, for some purposes, such as emphasizing information from videos or documents, judges tend to ask questions using a closed question pattern. The questions given only provide yes/no answer choices from the defendant.